Journalism in the Fallen Confederacy - Tuyll, Debra Reddin van. author. aut Link
VIII, 129 p.
Keywords: During the American Civil War, several newspapers remained Confederate sympathizers despite their locations being occupied by Union troops. Examining these papers, the authors explore what methods of suppression occupiers used, how occupation influenced the editorial and business sides of the press, and how occupation impacted freedom of the press.